Pentingnya Peralatan Bridge Simulator Kapal di Polimarin dalam Meningkatkan Ilmu Navigasi Mahasiswa Maritim dan Daya Saing Industri Kemaritiman - Erwin Sutantyo; Hero Budi Santoso (Jurnal Maritim Polimarin, 2018)
The role of the Bridge Ship Simulator at State Maritime Polytechnic of Indonesia has provided with navigation competences to enhancement for maritime students and how the competences of graduates maritime students can improve the competitiveness in the Indonesian maritime industry. This study aims to find out "How Bridge Simulator has provided Navigation Science competence improvement for maritime students and how the competence of maritime graduates can improve the competitiveness of the Indonesian maritime industry. The type of research in this study is an analytical description. The data sources is all graduates of Nautika study program in Polytechnic of Maritime Affairs of Indoneisa who already have certificate of Bridge Simulator. Data collection techniques are observation and interviews. Data analysis technique is qualitative analysis. There are three (3) of main parties studied in this study. The instructor as first party is related to the procurement of modules, schedule of training, communication in English with trainees, differences background of understanding of each participant, availability of time for training, different interpretations of IMO Model Course 1.22, as well as availability of number of instructors. The second party is the training participant, lack of introductory explanations towards training, scheduling, differences in participants' abilities, English language skills, and the seriousness of the trainees. The last party is stakeholder, the standard competency and current curriculum are not synchronized, graduates competence is still questionable, limited number of certified technicians, The industry need the graduduates ability to operate bridge simulators according to the type of fleet they have and difficulties because they have to find graduates that meet the desired standards. Recommendations made by the researchers are: procurement of modules and scheduling of quality and timely training, equalization of IMO Model Course 1.22 interpretation through Training for Trainers (TOT), pre-training debriefing of instructors and participants, better quality practical post tests to ensure competence of trainees.